Traditions of writing research - 4 0 16; Bazerman, Charles,;Krut, Robert,;Lunsford, Karen,;McLeod, Susan,;Null, Suzie,;Rogers, Paul; 5 (New York : Routledge, 2010)
A collection of papers that were presented at the Writing Research Across Borders conference that address writing initiatives, processes and practices in education.
Papers presented at the 2008 WRAB conference.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Study and teaching;Research;Study and teaching;Research;Research;Study and teaching;Research;Study and teaching;Research;Research -- Rhetoric;Rhetoric;Composition (Language arts);Written communication;Rhetoric;Rhetoric;Language arts;Written communication -- Congresses.;Congresses.;Congresses.;Congresses.;Conferences.;Conferences.;Conferences.;Conferences.; 20; 2